EFFECTS OF SOCIAL VULNERABILITY AND EDUCATION ON FRAILTY AND COGNITION THROUGH WORK CHARACTERISTICS. (11th November 2018) - Godin, J; Wallace, L; Theou, O; Andrew, M
Abstract: Background: Many jurisdictions are considering or have already increased pension eligibility age and more adults are remaining employed for longer. As such, understanding how work characteristics impact the health and well-being of older workers and the predisposing factors that may predict work quality is important. We sought to examine how education and social vulnerability are associated with job characteristics (i.e., job control, effort-reward imbalance) and, in turn, how job characteristics are associated with frailty and cognitive impairment. Methods: Participants were 3817 employed adults aged 50 years and older who participated in Waves 1 and 2 of the Survey of Health, Ageing, and Retirement in Europe. Using a structural equation modeling framework, we examined the direct and indirect effects – through job control and effort-reward imbalance - of education and social vulnerability on Wave 2 frailty and cognition. Results: Controlling for age and sex, social vulnerability had a direct effect, beta=0.23, p<.001, on frailty and direct, beta=0.15, p<.001, and indirect effects on cognitive impairment through job control, beta=0.03, p<.01, and effort-reward imbalance, beta=-0.03, p<.01. Education had a direct effect, beta=-0.19, p<.001, on cognitive impairment and indirect effects on frailty through both job control, beta=0.02, p< .01 and effort-reward imbalance, beta=-0.01, p<.05. Conclusion: We found that the characteristics of an older person's job may influence their health. Those with low levels of education and higher social vulnerability are more likely to have poor quality jobs (i.e., low control, high effort and low reward), which may lead to worsening frailty and cognition.